EVALUASI USER INTERFACE APLIKASI GOJEK TERHADAP PENGGUNA APLIKASI DI KOTA AMBON DENGAN METODE HEURISTIC - Tamtelahitu, Trientje Marlein; Lewaharilla, Nusye Mozes Y; Patty, Joanna Cristy (Majalah Ilmiah UNIKOM, 2020)
At this time the online motorcycle taxi application in Indonesia has grown and is experiencing rapid growth. This can be seen from the many online motorcycle taxi applications that have started providing services and information through an application, especially with a mobile application. Through this development, we can benefit from user involvement in using a good online motorcycle taxi application. Usability and credibility are believed to be one of the factors that influence the involvement of this development and growth. One of the ojegs based on mobile application technology used by the public is Go-Jek. Therefore, this paper presents an empirical study in evaluating the usability of the Go-jek mobile application. Software testing needs to be done so that it can be seen whether the software being developed meets the needs of end users. The results obtained show that knowing the severity of the application can be used to improve the Go-jek application. Key Words : Ambon, Mobile Application, Go-jek, Heuristic, Severity